(untitled) (Research, Society and Development, 2024)
The skin plays an extremely important role as a barrier and protection for humans and, when suffering an injury such as a burn, it must receive appropriate care. A burn represents a trauma that results in extreme damage, both physiological and metabolic, to the patient. After identifying the degree of injury suffered by the skin and carrying out a nutritional risk assessment, according to the severity of the burn found, it is possible to choose the best nutritional therapy to be applied. The objective of this study was to analyze nutritional therapy in the healing phase of burn patients and how it can help in the evolution of the patients’ condition. A bibliographical research was carried out using databases, using scientific articles from the last 30 years. Among the results, it was shown how the inflammatory events that occur in the burned patient’s body are a crucial part of the recovery process, but lead the patient’s body to enter a state of intensified catabolism, a condition in which the body begins to break down. their own energy reserves to face the crisis. This hypercatabolism can have long-lasting and potentially harmful effects on the patient’s body if not properly managed. To combat hypercatabolism and help the body recover, the patient must consume a significantly greater amount of calories and proteins than would normally be necessary, as well as micronutrients, such as zinc and selenium, which are compromised in cases of burns.